Modifiers of the effect of maternal multiple micronutrient supplementation on stillbirth, birth outcomes, and infant mortality: a meta-analysis of individual patient data from 17 randomised trials in low-income and middle-income countries - Emily R Smith, ScD; Anuraj H Shankar, ScD; Lee S-F Wu, MHS; Said Aboud, PhD; Seth Adu-Afarwuah, PhD; Hasmot Ali, MPH; Rina Agustina, PhD; Shams Arifeen, DrPH; Per Ashorn, PhD; Zulfiqar A Bhutta, PhD; Parul Christian, DrPH; Delanjathan Devakumar, PhD; et al. (Elsevier, 2017)
Background: Micronutrient deficiencies are common among women in low-income and middle-income countries. Data from randomised trials suggest that maternal multiple micronutrient supplementation decreases the risk of low birthweight and potentially improves other infant health outcomes. However, heterogeneity across studies suggests influence from effect modifiers. We aimed to identify individual-level modifiers of the effect of multiple micronutrient supplements on stillbirth, birth outcomes, and infant mortality in low-income and middle-income countries. Methods: This two-stage meta-analysis of individual patient included data from 17 randomised controlled trials done in 14 low-income and middle-income countries, which compared multiple micronutrient supplements containing iron-folic acid versus iron-folic acid alone in 112 953 pregnant women. We generated study-specific estimates and pooled subgroup estimates using fixed-effects models and assessed heterogeneity between subgroups with the χ2 test for heterogeneity. We did sensitivity analyses using random-effects models, stratifying by iron-folic acid dose, and exploring individual study effect. Findings: Multiple micronutrient supplements containing iron-folic acid provided significantly greater reductions in neonatal mortality for female neonates compared with male neonates than did iron-folic acid supplementation alone (RR 0·85, 95% CI 0·75-0·96 vs 1·06, 0·95-1·17; p value for interaction 0·007). Multiple micronutrient supplements resulted in greater reductions in low birthweight (RR 0·81, 95% CI 0·74-0·89; p value for interaction 0·049), small-for-gestational-age births (0·92, 0·87-0·97; p=0·03), and 6-month mortality (0·71, 0·60-0·86; p=0·04) in anaemic pregnant women (haemoglobin <110g/L) as compared with non-anaemic pregnant women. Multiple micronutrient supplements also had a greater effect on preterm births among underweight pregnant women (BMI <18·5 kg/m2; RR 0·84, 95% CI 0·78-0·91; p=0·01). Initiation of multiple micronutrient supplements before 20 weeks gestation provided greater reductions in preterm birth (RR 0·89, 95% CI 0·85-0·93; p=0·03). Generally, the survival and birth outcome effects of multiple micronutrient supplementation were greater with high adherence (≥95%) to supplementation. Multiple micronutrient supplements did not significantly increase the risk of stillbirth or neonatal, 6-month, or infant mortality, neither overall or in any of the 26 examined subgroups. Interpretation: Antenatal multiple micronutrient supplements improved survival for female neonates and provided greater birth-outcome benefits for infants born to undernourished and anaemic pregnant women. Early initiation in pregnancy and high adherence to multiple micronutrient supplements also provided greater overall benefits. Studies should now aim to elucidate the mechanisms accounting for differences in the effect of antenatal multiple micronutrient supplements on infant health by maternal nutrition status and sex. Funding: None.